Enabling Native Coexistence Between ICN and TCP/IP Architectures Over the Same Domain - Rosa, Eduardo Castilho; Silva, Flávio de Oliveira (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2020: Anais do XI Workshop de Pesquisa Experimental da Internet do Futuro, 2020)
Information-Centric Networking (ICN) has emerged as an alternative to overcome some issues imposed by TCP/IP architecture, such as the lackof mobility, security, and Quality-of-Service (QoS) native support. Seeing asTCP/IP will not disappear anytime soon, given the size of today’s Internet, mechanisms to coexist multiples ICN architectures along with TCP/IP are neces-sary. Through concepts like Network Function Virtualization (NFV), Software-Defined Networking (SDN) and Data Plane Programmability (DPP), we propose in this paper the FIACS, a system capable of allowing pairs of entitiesto communicate transparently with each other by using its L2 access link andnative protocols stacks over the same underline infrastructure.